A methodology for evaluating the economic risks of hurricane-related disruptions to port operations. (August 2022) - Balakrishnan, Srijith; Lim, Taehoon; Zhang, Zhanmin
Abstract: Among natural disasters, hurricanes pose significant threat to port infrastructure in the United States, especially to those along the coasts of the Atlantic Ocean and the Gulf of Mexico. The operational continuity of ports is critical because of the growing reliance of domestic and international businesses on ports and their significance in the growth of national and regional economies. While direct physical damages to ports are not rare, a shutdown of port operations is more likely declared by authorities as a precautionary and preparatory measure during hurricanes. Considering the enormous economic importance of ports and their vulnerability to hurricanes, the current study proposes a framework and methodology to analyze the economic risks of such hurricane-related shutdowns using hurricane- and port-related determinants. The risks of shutdowns are modeled using regression analysis based on historical port shutdown data and are combined with extensions of the well-known input–output model to predict the operational and economic risks of ports to hurricanes. The application of the methodology is demonstrated by conducting a case study based on the Texas Port System to evaluate the economic risks of hurricane-related port disruptions on the U.S. economy. Highlights: Presents a methodology to estimate economic risks of hurricane-related port shutdowns. The duration of hurricane-related port shutdowns is predicted using regression models. Economic impacts of port disruptions are predicted using input-output model.